A new paradigm in low-risk papillary microcarcinoma: active surveillance. (4th September 2017) - González Bóssolo, Alex; Garcia, Michelle Mangual; González, Paula Jeffs; Garcia, Miosotis; Villarmarzo, Guillermo; Martinez, Jose Hernán
Summary: Classical papillary thyroid microcarcinoma (PTMC) is a variant of papillary thyroid carcinoma (PTC) known to have excellent prognosis. It has a mortality of 0.3%, even in the presence of distance metastasis. The latest American Thyroid Association guidelines state that although lobectomy is acceptable, active surveillance can be considered in the appropriate setting. We present the case of a 37-year-old female with a history of PTMC who underwent surgical management consisting of a total thyroidectomy. Although she has remained disease-free, her quality of life has been greatly affected by the sequelae of this procedure. This case serves as an excellent example of how first-line surgical treatment may result more harmful than the disease itself. Learning points: Papillary thyroid microcarcinoma (PTMC) has an excellent prognosis with a mortality of less than 1% even with the presence of distant metastases. Active surveillance is a reasonable management approach for appropriately selected patients. Patients should be thoroughly oriented about the risks and benefits of active surveillance vs immediate surgical treatment. This discussion should include the sequelae of surgery and potential impact on quality of life, especially in the younger population. More studies are needed for stratification of PTMC behavior to determine if conservative management is adequate for all patients with this specific disease variant.